Psychology Of Yevhen Mileryan's Work: Between Ukraine And Armenia - Boltivets, Serhiy; Karapetyan, Vladimir; Kobylyanska, Iryna (Մանկավարժ հրատ․)
The article reveals the content and significance of multifaceted psychological Yevhen Oleksandrovych Mileryan's research works (1913 - 1983) − creator of measuring, training, cognitive, experimental, control psychological equipment, numerous methods of psychological selection of pilots, operators, drivers, the use of which allowed to prevent emergencies and catastrophes occurrence caused by people involved in the management of technical systems of different levels of complexity. The main milestones of the way of Ukrainian and Armenian scientist‘s life has been presented, to whose fate the trials of the World War II fell, variability of periods of creative self-realization and repressions, work in Ukraine and Armenia. This, in particular, the establishment of experimental workshops for the manufacture of psychological devices at the Research Institute of Psychology of the Ministry of Education of the USSR and creation in them the first "Device for demonstration of optical sensations and perception acording to the course of psychology", that allowed to demonstrate the patterns of color mixing, the phenomenons of contrast, including the phenomenon of marginal contrast and saturation, later - an electron-beam device for observing the dynamic picture of the spatial distribution of electric potentials, on the basis of which the activity changes of the cerebral cortex under the influence of various sound irritants in the presence or absence of attention directed at them have been studied, the bioelectrical activity of the brain during an electroconvulsive attack has been established. Հոդվածում բացահայտվում է Եվգենի Ալեքսանդրովիչ Միլերյանի (1913 - 1983 թթ.) բազմակողմանի հոգեբանական աշխատությունների բովանդակությունը և նշանակությունը. ինչը թույլ է տվել կանխել բարդության տարբեր մակարդակների տեխնիկական համակարգերի կառավարման մեջ ներգրավված մարդկանց կողմից առաջացած արտակարգ և աղետների առաջացումը: Ներկայացվել են ուկրաինացի և հայ գիտնականի կյանքի ճանապարհի հիմնական հանգրվանները, որոնց ճակատագրին են արժանացել Երկրորդ համաշխարհային պատերազմի փորձությունները, ստեղծագործական ինքնաիրացման և ռեպրեսիաների շրջանների փոփոխականությունը, աշխատանքը Ուկրաինայում և Հայաստանումֈ Սա, մասնավորապես, ԽՍՀՄ կրթության նախարարության հոգեբանության գիտահետազոտական ինստիտուտում հոգեբանական սարքերի արտադրության փորձարարական սեմինարների ստեղծումը և դրանցում առաջին «Սարքը օպտիկական սենսացիաների և ընկալման ցուցադրման համար՝ ըստ ընթացքի. հոգեբանություն», որը թույլ է տվել ցույց տալ գունային խառնուրդի օրինաչափությունները, հակադրության երևույթները, ներառյալ սահմանային հակադրության և հագեցվածության երևույթը, ավելի ուշ՝ էլեկտրական պոտենցիալների տարածական բաշխման դինամիկ պատկերը դիտարկելու էլեկտրոնային ճառագայթային սարքի հիմքի վրա: В статье раскрывается содержание и значение комплексных психологических работ Евгения Александровича Милерьяна (1913 - 1983). что предотвратило возникновение аварийных ситуаций по вине людей, задействованных в управлении техническими системами разного уровня сложности. Были представлены основные вехи жизни украинско-армянского ученого, судьба которого постигла испытания Второй мировой войны, вариативность периодов творческой самореализации, репрессий, работы в Украине и Армении. Речь идет, в частности, о создании экспериментальных семинаров по производству психологических устройств в Научно-исследовательском институте психологии Министерства образования СССР, на которых, согласно процессу, был продемонстрирован первый «Устройство для оптических ощущений». «Психология», позволившая показать закономерности смешения цветов, явления контраста, в том числе явление граничного контраста и насыщенности, позже наблюдать динамическое изображение пространственного распределения электрических потенциалов на основе электронного луча. Изучение изменений активности коры головного мозга при наличии или отсутствии к ним внимания под воздействием различных звуковых раздражителей подтвердило биоэлектрическую активность головного мозга при электросудорожной терапии. Есть документальные свидетельства очевидцев репрессий Е.О. Милерян и преследованием в Украине в начале 70-х годов 20 века.
Keywords: Psychophysiological experiments